2005
DOI: 10.1080/00016480510037915
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the morphology and calcium content of vestibular otoconia in rats after simulated weightlessness

Abstract: Reduction in bone formation may have been the main reason for the lower calcium content of the otoconia after simulated weightlessness in rats. The head-ward distribution of blood volume may explain the morphological changes observed in the middle and inner ears. To observe morphological changes in the vestibular organs and measure the calcium content of otoconia in rats after simulated weightlessness. We used a tail suspension model of simulated weightlessness and then investigated changes in the vestibular o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…To date, every rat or guinea pig study that has examined corticosterone or cortisol levels (respectively) following unilateral or BVD has found no significant difference compared to sham controls up 5 months post-op. (Gliddon et al, 2003; Lindsay et al, 2005; Zhang et al, 2005; Russell et al, 2006; Zheng et al, 2008). It is conceivable that BVD causes a long-term increase in glucocorticoids only in humans, as a result of the psychosocial impact of living without a balance system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, every rat or guinea pig study that has examined corticosterone or cortisol levels (respectively) following unilateral or BVD has found no significant difference compared to sham controls up 5 months post-op. (Gliddon et al, 2003; Lindsay et al, 2005; Zhang et al, 2005; Russell et al, 2006; Zheng et al, 2008). It is conceivable that BVD causes a long-term increase in glucocorticoids only in humans, as a result of the psychosocial impact of living without a balance system.…”
Section: Discussionmentioning
confidence: 99%
“…We considered that these smaller sample sizes were justified in this particular case, based on the precision of stereological analysis, which involves minimal measurement error and therefore reduces variation (Gundersen and Jensen, 1987; West and Gundersen, 1990; Zhang et al, 2005). Although averages across animals were used in the Section “Statistical Analyses” (see below), error in the estimates for individual animals contributes to the overall variation around the group means, and objective and precise counting procedures can minimize this error.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative, however, is that responses are dampened after repeated exposure because the high magnetic fields persistently alter or damage the peripheral vestibular apparatus. Prolonged or intense stimuli, such as chronic weightlessness [50, 51], rotation [52], changes in atmospheric pressure [53], or even a percussive auditory stimulus [54] can cause long-lasting damage to the semicircular canals or otolith organs. In Experiment 3 we observed a long-term decrement (after 36 days) in the induction of locomotor circling, although not in CTA acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Lindsay et al (2005) and Zhang et al (2005) assayed serum corticosterone at 10 h and 2 weeks post UVD in three groups of rats either having undergone surgical UVD, sham surgery, or no surgery (anesthetic control), and found no significant difference in serum corticosterone between groups. Lindsay et al (2005) additionally assessed serum corticosterone at 58 h and found that all groups had a significant decrease in corticosterone, while Zhang et al (2005) found that the 10-h serum corticosterone was higher in all groups when compared with the 2-week time-point (Lindsay et al, 2005; Zhang et al, 2005).…”
Section: Stress and Vestibular Compensation In Animal Studiesmentioning
confidence: 96%
“…Lindsay et al (2005) additionally assessed serum corticosterone at 58 h and found that all groups had a significant decrease in corticosterone, while Zhang et al (2005) found that the 10-h serum corticosterone was higher in all groups when compared with the 2-week time-point (Lindsay et al, 2005; Zhang et al, 2005). …”
Section: Stress and Vestibular Compensation In Animal Studiesmentioning
confidence: 99%